Heat transfer and fluid flow characteristics of a pair of interacting dual swirling flame jets impinging on a flat surface. (September 2018) - Singh, Parampreet; Chander, Subhash
Highlights: Interactions result in distortion of RCZ and inward deflection of inner flames. Intense mixing and turbulence in the interaction region causes high heat release. Co-swirling interacting flames results in development of tilted cross flow. Heat flux patterns on the impingement surface are governed by the distorted RCZ. Average heat fluxes of interacting swirling flames are higher than single flame. Abstract: Experimental and numerical studies have been conducted to investigate the flow field and heat transfer characteristics of a pair of dual interacting swirling flames impinging on a flat surface. Commercial computational fluid dynamics (CFD) code (FLUENT®) has been used to simulate the interacting isothermal swirling impinging jets. Inverse heat conduction procedure (IHCP) has been used to calculate the impingement heat fluxes from the surface temperatures captured by Infra-red camera. Effect of separation distance (H/Dh  = 2.5, 4, 6 and 8) and inter-jet spacings (S/Dh  = 4, 6, 8 and 10) have been studied at various Reynolds numbers ( Re (o) = 7000, 9000, 11000, 13, 000 and Re (i) = 700, 1000, 1300) under stoichiometric conditions. Strong interactions between adjacent dual swirling flames result in high heat transfer due to increased mixing and turbulence in the interaction region. The inner non-swirling flames are seen to deflect towards interacting side due to asymmetric interactions. Numerical simulation predicted this deflection to be primarily due to large recirculation bubble developed from asymmetric interactions. Tilted cross-flow, emerging from interaction region has been observed due to momentum exchange taking place between cross-flow and swirling flames (jets). Area weighted average of local heat flux and relative deviation from averaged value has been calculated at various H/Dh and S/Dh . High average heat fluxes are obtained at smallest H/Dh and S/Dh . It has been concluded that for a system of burners considered for the present study, H/Dh  = 2.5 and S/Dh  = 8 is the optimum configuration on the basis of minimum relative deviation.